VD_FINDINFO Arrêt / 2025 / 181 vom 28. März 2025 - VD Tribunal cantonal (2025)
ALLOCATION POUR IMPOTENT, ADMISSION DE LA DEMANDE, AVS | 43bis LAVS, 17 al. 2 LPGA, 9 LPGA, 37 RAI, 88a al. 2 RAI, 66bis RAVS